1997
DOI: 10.1021/bi962630c
|View full text |Cite
|
Sign up to set email alerts
|

Eucaryotic DNA Primase Does Not Prefer To Synthesize Primers at Pyrimidine Rich DNA Sequences When Nucleoside Triphosphates Are Present at Concentrations Found in Whole Cells

Abstract: The critical role of NTP concentration in determining where calf thymus DNA primase synthesizes a primer on a DNA template was examined. Varying the concentration of NTPs dramatically altered the template sequences at which primase synthesized primers. At the low NTP concentrations typically used for in vitro experiments (100 microM), primase greatly preferred to synthesize primers at pyrimidine rich DNA sequences. However, when the concentrations of NTPs were increased to levels typically found in whole cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…It follows that an increase in the concentration of a particular ribonucleotide might stabilize the Pol ␣-primase complex at different template sequences and thereby alter the initiation profile. Indeed, it has been reported that at elevated ribonucleotide concentrations, the Pol ␣-primase complex purified from calf thymus initiates synthesis in a sequence-independent manner (43). Therefore, we next addressed whether elevated ribonucleotide concentrations had similar effects on start site selection in the SV40 replication system.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…It follows that an increase in the concentration of a particular ribonucleotide might stabilize the Pol ␣-primase complex at different template sequences and thereby alter the initiation profile. Indeed, it has been reported that at elevated ribonucleotide concentrations, the Pol ␣-primase complex purified from calf thymus initiates synthesis in a sequence-independent manner (43). Therefore, we next addressed whether elevated ribonucleotide concentrations had similar effects on start site selection in the SV40 replication system.…”
Section: Resultsmentioning
confidence: 98%
“…In order for primase to initiate DNA synthesis, a stable complex must form between primase and the pyrimidine-rich initiation sites. Recent experiments indicate that stable binding of two NTPs to primase is a prerequisite for stable complex formation between primase and single-stranded DNA templates (43,64). Related studies demonstrated that fluctuations in ribonucleotide pools can influence exactly which template sequences are selected as initiation sites (43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations